2D Elasticity solution for sandwich panels with functionally graded lattice cores. (15th November 2022) - Georges, H.; Meyer, G.; Mittelstedt, C.; Becker, W.
Abstract: The quest for weight-reduced components while maintaining strength requires new structures and lightweight concepts that promise more advantages than existing structures. In sandwich panels, improving the mechanical performance of the face sheets is almost exhausted due to using ultra-high-strength materials. By contrast, the sandwich core offers a high light-weight potential when it constitutes the largest part of the total weight of the sandwich. Novel structures such as lattices can significantly enhance the core's mechanical performance. Lattice structures fabricated by additive manufacturing (AM) provide comparable mechanical properties to honeycombs and allow multifunctional use of the core. Another benefit of using AM is the ability to customize the core mechanical properties. Such a design could be achieved by using a functionally graded lattice core. In this work, an analytical model is derived to determine stresses and deformations in graded lattice cores of sandwich panels. Compared to the classical sandwich theory, the presented model enables the determination of the out-of-plane stresses near the load application areas. Furthermore, evaluating the stresses in the lattice struts of the graded core highlights the benefits of using graded cores in sandwich panels since the stress in graded cores exhibits a more homogeneous distribution, enabling better material exploitation. Highlights: Analytical modeling of strut-based lattice cores in sandwich panels using homogenization and dehomogenization methods. Reduction of the computational effort compared to FE modeling. Determination of localized stresses and deformations in the core. Grading the strut diameter to adapt the stress distribution in the core. Increase the strength-to-weight ratio of the structure.